Hedonic Modeling for Fed Cattle Price Reporting and Market Transparency - Jason Franken; Haluk Gedikoglu; Theodoros Skevas; Mary Hendrickson (Applied Economic Perspectives and Policy, 2026)
ABSTRACT The Livestock Mandatory Reporting Act of 1999 was enacted to facilitate price reporting and increase market transparency. With immense structural change in the cattle industry, current practices of reporting weighted average prices are becoming less meaningful. Recent studies indicate that with the collection of additional data beyond what is currently available under the act, hedonic modeling may hold potential to facilitate more meaningful price reporting. This study revisits the issue using transaction level prices from four beef packers and finds incorporating the recommended information improves hedonic models' representation of prices. Though improved model specification enhances coefficient consistency, with particularly promising results for quality grades, remaining variation in sign and significance of other daily estimated coefficients undermines the approach's ability to inform intuitive premiums and discounts for some characteristics. Future research may explore on balance the relative merit of further improvement in data collection, model specification, and increasing observations with longer multiday rolling regressions to facilitate price reporting.